Face-Fusion of Icosahedral Boron Hydride Increases Affinity to γ-Cyclodextrin: closo,closo-[B21 H18 ]- as an Anion with Very Low Free Energy of Dehydration - Assaf, Khaleel I; Holub, Josef; Bernhardt, Eduard; Oliva-Enrich, Josep M; Fernández Pérez, M Isabel; Canle, Moisés; Santaballa, J Arturo; Fanfrlík, Jindřich; Hnyk, Drahomír; Nau, Werner M (Chemphyschem, 2020)
The supramolecular recognition of closo,closo-[B21 H18 ]- by cyclodextrins (CDs) has been studied in aqueous solution by isothermal titration calorimetry and nuclear magnetic resonance spectroscopy. These solution studies follow up on previous mass-spectrometric measurements and computations, which indicated the formation and stability of CD ⋅ B21 H18- complexes in the gas phase. The thermodynamic signature of solution-phase binding is exceptional, the association constant for the γ-CD complex with B21 H18- reaches 1.8×106 M-1 , which is on the same order of magnitude as the so far highest observed value for the complex between γ-CD and a metallacarborane. The nature of the intermolecular interaction is also examined by quantum-mechanical computational protocols. These suggest that the desolvation penalty, which is particularly low for the B21 H18- anion, is the decisive factor for its high binding strength. The results further suggest that the elliptical macropolyhedral boron hydride is another example of a CD binder, whose extraordinary binding affinity is driven by the chaotropic effect, which describes the intrinsic affinity of large polarizable and weakly solvated chaotropic anions to hydrophobic cavities and surfaces in aqueous solution.
Keywords: anion binding; boron clusters; desolvation; intermolecular interactions; host-guest chemistry